Strategi Konten Video Pendek Sosial Media ANTARATV untuk Liputan Acara Film Baru - Anargya Atha; Alfa Taufan Latif (CV. ITTC INDONESIA, 2026)
News media organizations face increasing pressure to adapt their content strategies to social media platforms; however, research examining how national news agencies produce short-form video content for film coverage remains limited. This study aims to analyze AntaraTV’s strategy in producing video content for coverage of new film events on social media. This study employs a descriptive qualitative approach through active participation and interviews with three informants: the Head of AntaraTV’s social media division, an intern content creator, and a film journalist. Data analysis utilizes data triangulation. The findings indicate that AntaraTV implements a comprehensive strategy based on Attention Economy Theory and Uses and Gratification Theory, focusing on short-form content lasting 30–60 seconds, publication timing aligned with film embargoes, and multi-platform distribution via Sprout Social on TikTok, Instagram, YouTube, and SnackVideo. Key challenges include balancing subjectivity and objectivity in film reviews, tight deadlines, and technical constraints such as inconsistent audio quality and volume. This strategy has proven effective in promoting films and providing comprehensive information, although AntaraTV’s content tends to be more formal and lacks the emotional appeal found in independent media or reviews